Systemic cellular immune response in Helicobacter pylori associated duodenal ulcer and chronic antral gastritis - Hakan YÜCEYAR; Murat SARUÇ; Ali KOKULUDAĞ; Ender TERZİOĞLU and Gamze GÖKSEL and Aydın İŞİSAĞ (Turkish Journal of Gastroenterology, 2019)
-